If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -3)(x + 4) = -6 Reorder the terms: (-3 + x)(x + 4) = -6 Reorder the terms: (-3 + x)(4 + x) = -6 Multiply (-3 + x) * (4 + x) (-3(4 + x) + x(4 + x)) = -6 ((4 * -3 + x * -3) + x(4 + x)) = -6 ((-12 + -3x) + x(4 + x)) = -6 (-12 + -3x + (4 * x + x * x)) = -6 (-12 + -3x + (4x + x2)) = -6 Combine like terms: -3x + 4x = 1x (-12 + 1x + x2) = -6 Solving -12 + 1x + x2 = -6 Solving for variable 'x'. Reorder the terms: -12 + 6 + 1x + x2 = -6 + 6 Combine like terms: -12 + 6 = -6 -6 + 1x + x2 = -6 + 6 Combine like terms: -6 + 6 = 0 -6 + 1x + x2 = 0 Factor a trinomial. (-3 + -1x)(2 + -1x) = 0Subproblem 1
Set the factor '(-3 + -1x)' equal to zero and attempt to solve: Simplifying -3 + -1x = 0 Solving -3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = 0 + 3 -1x = 0 + 3 Combine like terms: 0 + 3 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3Subproblem 2
Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2Solution
x = {-3, 2}
| 4(5y-8)-3y= | | 3(x+3)=4(1+x) | | 2(x+3)=3x-1 | | -1-6m= | | 15m=50m+40000 | | 2a-5=13 | | 4-(3-x)=2 | | 6=-1(7-c) | | k/21=15 | | 7y+2(y-3)=6(y+1)-4 | | 3.8-4.9x+0.1x=2.4y+0.2 | | -17+x=-9 | | 11a^2-9ab+4a= | | 6u-2u+12u=-16 | | 8+2x=20-4x | | -2(-7x+1)=5x+34 | | 7+3g-4h+3h-10= | | -9=17x | | 16=2(d-5) | | 3+6x=4x-7 | | 4x-4b=1x | | -4q-2=-18 | | -17*x=-9 | | 1.25p-0.2p+12=6 | | 5-4x=5-5x | | -7(-v-11)-v=-11(9v-7) | | (X^2)-6x-23=0 | | 6d-6d+5d+1=16 | | 45=12+3(t-8)-6 | | -2x=8.8 | | 4(-9)-70=12(-9)+2 | | 3(65)=(65)+10 |